Second World War spending and local economic activity in US counties, 1939–581. (28th February 2013) - Fishback, Price; Cullen, Joseph A.
<x xml:space="preserve">Abstract</x> Studies of the development of local economies often point to large‐scale Second World War military spending as a source of economic growth, even though spending declined sharply after demobilization. We examine the relationship between war spending per capita and the changes in economic activity in US counties between 1939 before the war and a period several years after the war. In the longer term counties receiving more war spending per capita during the war experienced greater population growth, but growth in per capita measures of economic activity showed little relationship with per capita war spending.